PHYTOCHEMISTRY AND BIOLOGICAL ACTIVITY OF PRIMULA SPECTABILIS TRATT., AN ENDEMISM OF VALVESTINO (ITALIAN ALPS) - Vitalini, S.; Fico, G.; Valaguzza, A.; Visioli, F.; Tomè, F. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Valvestino (Brescia) is a valley of Italian Central Southern Alps, recognized by European Union as “Site of Community Interest”; this site is characterized by the presence of numerous endemisms, some of them included in the IUCN Red List. An ethnobotanical investigation in this valley has pointed out that some species belonging to Primula genus are commonly used for their medicinal properties. In this work we report the flavonoid composition of the endemism Primula spectabilis Tratt. and its antioxidant potential.Samples of this species were collected during the summer of 2007 and determined according to “Flora d’Italia” by Pignatti. The dried powdered leaves were exhaustively extracted with increasing polarity solvents: n-hexane, dichloromethane, dichlorometane:methanol (9:1) and methanol. The methanol extract was chromatographed on Sephadex LH-20, using MeOH as eluent, to obtain fractions that showed NTS-PEG positive spots on TLC. Finally some of these fractions have been submitted to RP-HPLC to obtain phenols, and the structural identification was determined on the basis of extensive NMR spectral studies, as well as by HPLC-MS analysis. Three compounds (C-glucosides of kaempferol, quercetin and apigenin), never isolated before in the Primula genus, were identified. The methanol extract, the richest in polyphenols, was also submitted, after the determination of polyphenolic content by the Folin-Ciocalteau method, to DPPH, total antioxidant capacity based upon the reduction of Cu++ to Cu+ and FRAP assays. The obtained results showed a considerable antioxidant activity from P. spectabilis.